The Application Of Ai-Based Digital Marketing And Customer Satisfaction: Implications For Customer Loyalty - Syaifuddin Syaifuddin (UNIVERSITAS PAKUAN, 2025)
In the growing digital era, the application of technology in marketing is important to increase customer loyalty. This study aims to examine the effect of artificial intelligence (AI)-based digital marketing implementation and customer satisfaction on customer loyalty at the Bandung Wholesale Centre. This research uses a quantitative approach with a descriptive and analytical design. The population in this study were customers and merchants operating in the Bandung Wholesale Centre, with purposive sampling technique, involving 150 respondents (100 customers and 50 merchants). The location of this research was at the Bandung Wholesale Centre, and the research was conducted within a span of two months. The analysis technique used is descriptive analysis to describe the characteristics of respondents and multiple linear regression to test the relationship between variables. The results showed that the application of AI-based digital marketing and customer satisfaction did not have a significant influence on customer loyalty. This finding indicates that price and product quality factors are more dominant in influencing customer loyalty in traditional wholesale centres. The implication of this study is that while technology can improve customer experience, grocery centre managers need to focus on basic aspects such as price and product quality to increase customer loyalty.